The Different Characteristics of Cirrus Optical Coherence Tomography between Superior Segmental Optic Hypoplasia and Normal Tension Glaucoma with Superior Retinal Nerve Fiber Defect - Jong Chul Han; Da Ye Choi; Changwon Kee (Journal of Ophthalmology)
Purpose. To evaluate the different characteristics in superior segmental optic hypoplasia (SSOH) and normal tension glaucoma (NTG) with superior retinal nerve fiber layer (RNFL) defect (NTG-SRD) compared to normal control using cirrus optical coherence tomography (OCT). Methods. SSOH eyes and NTG-SRD eyes were reviewed. The peripapillary RNFL (pRNFL) and ganglion cell inner plexiform layer (GCIPL) of the two groups were compared to age-matched normal controls using cirrus OCT. Results. Included in this study were 31 SSOH eyes, 33 NTG patients, and 49 healthy normal controls. Compared to normal controls, pRNFL thickness in SSOH eyes was thinner except in the inferotemporal to the temporal segment. NTG-SRD eyes had thinner pRNFL except in the nasal to inferonasal segment. Meanwhile, GCIPL thickness in SSOH eyes was thinner in the global and sectoral segment, but not in the superonasal and inferonasal sectors compared to normal controls. NTG-SRD eyes showed thinner GCIPL in all sectors compared to normal controls. In case of comparison between SSOH and NTG-SRD, superonasal sector was thinner in NTG-SRD than in SSOH (P=0.03). Conclusions. The different distributions of nerve fiber layer were shown in pRNFL and GCIPL between SSOH eyes and NTG-SRD eyes.